2018
DOI: 10.1007/s00018-018-2961-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics and metastasis

Abstract: Changes in cellular metabolism are now a recognized hallmark of cancer. Although this process is ripe with therapeutic potential in the clinic, its complexity and extraordinary plasticity have systematically defied dogmas and oversimplifications. Perhaps best exemplifying this intricacy is the role of mitochondria in cancer, which in just a few years has gone from largely unnoticed to pivotal disease driver. The underlying mechanisms are only beginning to emerge. However, there is now clear evidence linking th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 90 publications
3
48
0
Order By: Relevance
“…Myc-mitochondrial signaling enables tumor cell motility. Recent studies have shown that mitochondrial trafficking to the cortical cytoskeleton fuels tumor cell movements (20). Consistent with this possibility, Myc silencing suppressed focal adhesion (FA) complex dynamics in PC3 cells (Fig.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Myc-mitochondrial signaling enables tumor cell motility. Recent studies have shown that mitochondrial trafficking to the cortical cytoskeleton fuels tumor cell movements (20). Consistent with this possibility, Myc silencing suppressed focal adhesion (FA) complex dynamics in PC3 cells (Fig.…”
supporting
confidence: 68%
“…A role of Myc in this process has remained controversial in the literature (37), as oncogenic Myc has been linked to inhibition of tumor cell invasion via suppression of Jun N-terminal protein kinase (JNK) activity (38) or sensitization to transforming growth factor ␤ (TGF-␤) signaling (39). Conversely, the data presented here showing that Myc transcriptionally controls an integrated cellular machinery for mitochondrial movements, which in turn fuels cell motility and invasion (20), points to this pathway as a ubiquitous aspect of Myc-driven tumors, important for metastatic competence, in vivo. In this context, mitochondrial trafficking to the cortical cytoskeleton at the leading edge of migration has been proposed as an efficient, "spatiotemporal" energy source to fuel membrane lamellipodium dynamics, persistent phosphorylation of cell motility kinases, and heightened tumor chemotaxis and invasion (23)(24)(25).…”
Section: Discussionmentioning
confidence: 94%
“…While the downregulation of mitochondrial pathways is a common feature of metabolic rewiring across invasive cancer cells and is a poor prognostic indicator 50 , these studies focus on the bulk of the tumor cell population and would likely not detect rare, specialized subpopulations that are sensitive to mitochondrial inhibitors 51 . Maintaining intact mitochondrial function is considered essential for cancer cell invasion and metastasis to occur 52,53 , and enhanced OXPHOS, mitochondrial biogenesis, and oxygen consumption rates are observed in invasive breast cancer and pancreatic cancer [54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…These organelles are responsible for driving cell life and death through mitochondrial network structure homeostasis, which is determined by a balance of fission and fusion [1]. Mitochondrial fission is important for maintaining cellular functions, including cellular development and homeostasis, and apoptosis [2,3]. The cytoplasmic dynaminrelated GTPase Drp1 plays a key role in the regulation of mitochondrial fission.…”
Section: Introductionmentioning
confidence: 99%